Urgensi Kompetensi Penyuluh Pertanian dalam Pemberdayaan Kelompok Tani Lada di Perbatasan Kalimantan Barat - Komariyati, Komariyati; Kurniady, Dedy; Nugraha, Aditya (Fakultas Pertanian Universitas Tanjungpura, 2024)
The Urgency of Agricultural Extension Competence in Empowering Pepper Farming Groups on the Border of West Kalimantan. The aim of the research is to describe the urgency of the competency of agricultural instructors in the context of empowering pepper farmer groups on the West Kalimantan border. The type of research is descriptive qualitative. Research data is primary and secondary data. Validate data by triangulating sources and methods. The data analysis technique uses interactive analysis. The results of the research conclude: (1) The target of the extension program is to increase the empowerment of pepper farmer groups, so that pepper farmers receive various information about pepper cultivation so that their production increases and at the same time their income increases; (2) Agricultural extension programs can be successful if they are based on the principles of community empowerment which include: Integrated Development, Human Rights, Sustainability, Empowerment, Self- Reliance, Organic Development, The Integrity of Process, Co-operation, and Participation; (3) The competence of extension workers has a very important contribution in determining the success of the extension program or empowerment of pepper farmers, because the competence of extension workers will increase the competence of farmers in the aspects of knowledge, skills and active participation in managing farmer groups.